Ecotourism and biodiversity conservation - Rai, Suresh Chand, 1958- (Tourism and hospitality development and management., 2012)
Tourism is the most important non-farm activity in the mountainous region. In mountain belts the aesthetic value of the land is by itself one of the critical assets for the otherwise impoverished communities. The growth of population and the increasing demand at the individual level of various non-farm items have expanded the demand of goods beyond the traditional technological practices of mountain community and their cultural sensitivities. These initiatives of the government have only mirrored Western models of tourism development rather than developing appropriate, need-based strategies for harnessing the economic potential. This new book examines ecotourism and biodiversity conservation.